Students’ perspective on genomics: from sample to sequence using the case study of blueberry - Mudd, Austin B.; White, Elizabeth J.; Bolloskis, Michael P.; Kapur, Nicholas P.; Everhart, Koyt W.; Lin, Ying-Chen; Bussler, Weston W.; Reid, Robert W.; Brown, Ryan H. (Frontiers in Genetics, 2013)
Advances in genomic sequencing technologies in the past decade have revolutionized the field of genomics, resulting in faster and less expensive sequencing. Holding back the potential for innovation, however, is a widespread lack of understanding of genomics and sequencing by the general public. In an attempt to remedy this problem, this paper presents an introduction to the fields of genomics, bioinformatics, and proteomics using the blueberry genome as a model case study of the plant genomics field. The blueberry (Vaccinium sect. Cyanococcus) is often cited as a “super food” in the media due to its nutritional benefits and global economic importance. There have been a number of related genomic publications in the past 20 years; however, a completed genome and a full analysis into the health-related pathways are still needed. As exemplified by this blueberry case study, there are opportunities for future genomic research into numerous beneficial plant species. The solid background presented in this paper provides future researchers the foundation to explore these uncharted areas.